Coal and gas outburst features in Guizhou mining areas and its prevention countermeasures - KONG Que; WU Guiyi; ZHONG Feng; CHEN Jiming (Gong-kuang zidonghua, 2016)
With collection and analysis of outburst indexs in 381 mines and 695 seams and 214 coal and gas outburst accidents occurred in 120 mines in Guizhou mining areas, a study on coal and gas outburst index distribution features and outburst features in Guizhou mining areas was conducted, and relative outburst prevention countermeasures were proposed. Enhanced coal seam outburst index measurement, developing strict management system to mining areas with high outburst strength and more outburst such as Qianbei, Zhina, Liuzhi, Panjiang and Shuicheng, enhanced outburst prevention work of coal roadway heading face, and enhanced blasting management, dynamic phenomenon monitoring and geological structure detecting could be applied to reduce coal and gas outburst accidents occurred in Guizhou mining areas.